2013
DOI: 10.1590/s0034-737x2013000500018
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da aplicação foliar de silicato de potássio e de fungicida na severidade da ferrugem da folha e da mancha amarela do trigo

Abstract: Effect of foliar application of potassium silicate and fungicide on the severity of leaf rust and yellow leaf spot in wheatThe occurrence of diseases such as leaf rust (Puccinia triticina) and yellow spot (Drechslera tritici-repentis) can decrease wheat yield. This study aimed to evaluate the effect of foliar application of potassium silicate (PS) and fungicide on the control of leaf rust and yellow spot in the cultivars Safira and Quartzo. The experiment was carried out in a randomized complete block split-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In this attribute, both cultivars that received silicon exhibited higher quality and yield, when compared to treatments without the addition of the micronutrient, which once again indicates the beneficial effect of its use. These results also corroborate those presented by Soratto et al (2012), Wordell Filho et al (2013, Telaxka et al (2019) and Galindo et al (2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this attribute, both cultivars that received silicon exhibited higher quality and yield, when compared to treatments without the addition of the micronutrient, which once again indicates the beneficial effect of its use. These results also corroborate those presented by Soratto et al (2012), Wordell Filho et al (2013, Telaxka et al (2019) and Galindo et al (2021).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding tan spot, Wordell Filho et al (2013) reported that the association of fungicides and potassium silicate provided smaller areas under the progress curve in an experiment carried out in Chapecó in the state of Santa Catarina, Brazil. The results of the present work also corroborate those of Pazdiora et al (2017), where in an experiment under controlled conditions, there was greater resistance to tan spot even in susceptible cultivars; however, the greatest reduction in tan spot was in moderately resistant cultivar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation